Information-seeking behavior and information needs of diocesan seminarians, religious and lay students of St. Vincent School of Theology - Urcia, Maylene U. (School of Library and Information Studies, University of the Philippines Diliman, 2009)
Information seeking is important to satisfy one's information needs. Information needs vary and may result to different information-seeking behavior. Information can be found in multiple sources. There are several factors that affect the choice of information source such as reliability, relevance, scope and novelty of the information contents. Availability and access also affect the choice of an information source. Online information seeking is popular among different disciplines in the society.